Mathematics for the IB diploma. Higher level topic 10, series and differential equations - Neill, Hugh.; Quadling, D. A. (Cambridge, UK ; New York : Cambridge University Press, 2008)
Provides learning objectives, concept explanations, worked examples, review exercises, and answers correlated to the higher level topic ten, series and differential equations, syllabus of the International Baccalaureate Diploma Programme.
Includes index.
Adult.
Adult
Keywords: International baccalaureate -- Study guides; Mathematics -- Problems, exercises, etc; Mathematics -- Examinations -- Study guides; International baccalaureate -- Study guides; Mathematics -- Problems, exercises, etc; Mathematics -- Examinations -- Study guides